INNER CONFLICT AND IDENTITY CRISIS IN MUDWOMAN BY JOYCE CAROL OATES - Oysuluv Muhammadova; Elmanova Mastura Toshnazarovna (Western European Studies, 2026)
This article examines the themes of inner conflict and identity crisis in Joyce Carol Oates’s novel Mudwoman (2012). Reading the novel through psychoanalytic and feminist lenses, the study explores how memory, trauma, and social expectation shape the protagonist M.R. Neukirchen’s fractured subjectivity. Mudwoman stages identity as layered and unstable: present-day success overlays a childhood of violence, abandonment, and near-drowning that returns as intrusive visions and compulsive behavior. This paper argues that Oates uses gothic imagery, dream logic, and campus satire to depict identity as a site of ongoing conflict in which personal history resists erasure. The analysis proceeds in three parts: (1) trauma and memory as formative forces in identity; (2) the novel’s formal strategies for representing inner conflict; and (3) social and institutional pressures that exacerbate identity crisis. The article concludes that Mudwoman advances contemporary American psychological fiction by insisting identity is both socially constructed and psychically haunted.
Keywords: Joyce Carol Oates; Mudwoman; identity crisis